1963
DOI: 10.1302/0301-620x.45b4.770
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Histochemical Studies on the Organic Constituents in Fracture Repair in Rats

Abstract: 1. The process of repair after fracture of the humerus of the growing rat has been studied by histological, histochemical and biochemical methods. 2. Both periosteal and surrounding mesenchymal cells take part in the process of repair. 3. The primary framework of collagen bridging the gap is mainly formed by the mesenchymal cells, while calcification and ossification of the framework is largely a function of the periosteum. 4. The mucopolysaccharide content rises rapidly in the first week after injury, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

1968
1968
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
2
18
0
3
Order By: Relevance
“…1, 2). Previous studies showed that the increase of the hydroxyproline level in the normal healing of fractures begins at the end of week 1, reaches its peak in week 3, and then gradually decreases to its normal level [2, 3,6,8,11,17[. The present study reveales similar results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1, 2). Previous studies showed that the increase of the hydroxyproline level in the normal healing of fractures begins at the end of week 1, reaches its peak in week 3, and then gradually decreases to its normal level [2, 3,6,8,11,17[. The present study reveales similar results.…”
Section: Discussionsupporting
confidence: 90%
“…They were anaesthetized with ether, and a simple method described in detail before [6,8,11,15,17] was used to produce manually a standard fracture of the lower midshaft of the tibia. The type and location of the fracture were determined by X-ray pictures.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand the total dry weight increased significantly in the group treated with 0.125 pg of la-OH-D,. In a previous study it has been observed histologically that Vitamin D, accelerates the organic phase of fracture repair (Udupa & Prasad 1963).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, Vitamin D has been found to stimulate the differentiation of the osteogenic cell layer of the periosteum of the radius in adult guinea-pigs during fracture healing (Grauer 1932). Vitamin D was also found to display a special selective effect on the organic phase of bone healing in rats (Udupa & Prasad 1963) and on the mineralization of autogenous bone grafts in rabbits (Donatelli et al 1962) and further to accelerate the initial mineralization in fracture repair of rats (Steier et al 1967).…”
mentioning
confidence: 99%
“…www.bjournal.com.br injury (14)(15)(16)(17). The initial hematoma after injury is important as a source of molecules that stimulate inflammation and proliferation.…”
Section: Introductionmentioning
confidence: 99%